Computer-aided design-CAM-guided endodontic microsurgical localization and retrieval of two separated instruments from the periapical area of a mandibular second molar - Akshayraj Langaliya; Ekta Chaudhari; Axita Patel; Jinali Shah (Wolters Kluwer Medknow Publications, 2021)
Three-dimensional (3D) imaging devices used for the visualization of anatomic structures not only allow for a more accurate diagnosis but also facilitate precise planning of surgical treatments, such as in guided surgery for instrument retrieval using templates. The innovative template-based treatment methods could also play a crucial role in future modern surgical endodontic treatments, enabling exact preplanning and precision-guided surgical interventions, and resulting in greater accuracy and success rates. We present here a case of a patient with a periapical lesion below a right mandibular second molar, with a fractured file segment extruding beyond the apex in the distal canal, and another instrument half-way extruded from the mesial canal, with radiolucencies evident at the mesial and distal root apices. The patient was treated by employing a 3D-guided microsurgical approach. First, 3D optical scans were imported into a guided surgery program. Periapical lesions and extruded fractured instruments were marked within the software. The osteotomy size, apical resection level, and bevel angle were defined pretreatment. This case introduces a novel-guided microsurgical endodontic technique, incorporating recommended guidelines of modern surgical endodontic treatment with the aid of 3D-printed surgical templates, by which minimally invasive surgical treatment was ensured with preservation of tooth, bone, and surrounding anatomical structures.